Reduction in Specific Consumption of Fuel in Gas-Cementation Furnaces - A. P. Nesenchuk; O. G. Fomenko; D. I. Shclovchik; T. V. Ruzhova; Z. B. Aidarova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers the possibility to reduce specific consumption of fuel in furnaces used for gas-cementation of steel products owing to product arrangements in operational space of preliminary heating and cementation zones.Simplified methodology is given to calculate time for preliminary heating of unspecified- shape products.